Organisational justice and workplace social support as predictors of employee wellbeing: A case of high-income workers in South Africa - Viljoen, Lana (Organisational Psychology, 2023)
Amongst the 17 Sustainable Development Goals as proposed by the United Nations, the study was concerned with promoting decent work (Sustainable Development Goal 8) and wellbeing (Sustainable Development Goal 3) amongst high-income workers. In line with what constitutes decent work, the study aimed to determine to what extent organisational justice (comprising distributive, procedural, interpersonal, and informational justice) and workplace social support (comprising perceived organisational support, perceived supervisory support, and perceived co-worker support) predicted employee wellbeing amongst high-income workers. The results provided insight into the multidimensionality of wellbeing and revealed two types of wellbeing present in the study, namely work-related wellbeing and interpersonal wellbeing. The study adopted a correlational research design, assisted by survey research, where an online survey was distributed via LinkedIn and WhatsApp to collect data from high-income workers (N = 120). The regression results indicated that all types of organisational justice and workplace social support predicted the two types of wellbeing. In addition, mediation analyses indicated that supervisory support strengthened the relationship between interactional justice (i.e., interpersonal and informational justice) and employee wellbeing (i.e., work-related and interpersonal wellbeing). The study thus highlighted the importance of supervisory support in achieving interpersonal and informational justice and proposed training aimed at interpersonal skills for supervisors to aid in the management of employee wellbeing. In addition, the study highlighted how COVID-19 had disintegrated the workplace as many organisations required their employees to work remotely. The study thus proposed that organisations should seek ways for employees to interact with one another in a virtual working environment. Therefore, as organisations maintain decent working conditions by implementing fairness and support in the workplace, they contribute to the management of employee wellbeing.